Fetal umbilical artery Doppler pulsatility index as a predictor of cardiovascular risk factors in children – a long-term follow up study. (November 2014) - Mone, F.; Thompson, A.; Stewart, M. C.; Ong, S.; Shields, M. D.
Abstract Objective: To determine if high umbilical artery Doppler (UAD) pulsatility index (PI) is associated with cardio-vascular (CV) risk-factors in children at age 12 years. Methods: We studied 195 children at age 12 years who had had in-utero UAD studies performed at 28 weeks' gestation. The children were grouped according to whether their umbilical Doppler PI was high (indicating poor feto-placental circulation) or normal. At age 12 years we assessed CV risk factors, including anthropometric measures, blood pressure, pulse wave velocity (a measure of arterial compliance), cardio-respiratory fitness, and homocysteine and cholesterol serum levels. Results: Compared with children with a normal UAD PI (N = 88), the children (N = 107) with high UAD PI had higher resting pulse rate (p = 0.04), higher pulse wave velocity (p = 0.046), higher serum homocysteine levels (p = 0.032) and reduced arterial compliance (7.58 versus 8.50 m/s, p = 0.029) using univariate analysis. These differences were not present when adjusting for cofounders was modeled. Conclusion: High PI on UAD testing in-utero may be associated with increased likelihood of some CV risk factors at age 12-years but confounding variables may be as important. Our study raises possible long-term benefits of in-utero UAD measurements.